Trend Analysis of Character Education in Mathematics Learning in Indonesia Over A Decade - Yuni Fitriyah; Wahyudin Wahyudin; Turmudi Turmudi; Hanifah Nurhayati; Fitria Maghfiroh (EduMa: Mathematics education learning and teaching, 2024)
Character education is a critical component in 21st-century education, serving not merely as a means to foster academic dimensions, but also as a foundational cornerstone in shaping moral and ethical values among students. This study aims to conduct a bibliometric analysis of recent developments and trends in character education research in mathematics learning in Indonesia over the past decade. The method utilized was bibliometric analysis, primarily condu cted through searches in the Dimensions database using the phrases "character education" and "mathematics education," following the PRISMA method. A total of 166 eligible articles were identified. Primary data were analyzed using Microsoft Excel and Mendeley's VOSviewer. The results indicated that publications related to character education in mathematics education in Indonesia fluctuated during 2014-2023, with the highest number of publications occurring in 2023. Semarang State University emerged as the institution with the most publications. The highest number of published articles came from the "Journal of Physics: Conference Series," while research demographics primarily focused on Central Java Province. Rochmad from Semarang State University was identified as the most influential author. Lastly, collaborative research primarily centered on "character education," with a particular emphasis on "Islamic values" and "learning materials," suggesting potential avenues for further investigation